KOMUNIKASI POLITIK ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH KOTA PEKANBARU FRAKSI GOLKAR PERIODE 2014-2019 DALAM MEMPEROLEH SUARA (STUDI PADA DAERAH PEMILIHAN IV) - Setiawati, Tutuko Darma; Nasution, Belli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
In the legislative elections that took place in Pekanbaru City in 2014-2019 period the Pekanbaru City House of Representatives held a new legislative election, in which elections were held in many electoral districts, one of them in the electoral district IV (Dapil IV) located in Marpoyan Damai sub-district and Bukit Raya, from the number of party factions participating in the legislative elections of the Golkar faction were the ones who got the most votes. Golkar faction get the most votes for 7 seats of member of Dpril which divided in Dapil I, Dapil II, Dapil III, Dapil IV, and Dapil V from each Dapil. Dapil IV is the first highest voice of Golkar faction, Drs. H. Tarmizi Muhammad and the third highest voice of the Golkar faction, Mr. H. Herwan Nasri, S.T.This study uses descriptive analysis with qualitative approach, where data collected in the form of words, images and not the numbers. the selection of informants was done by purposive sampling technique by placing the people directly related to DPRD Member of Pekanbaru City Golkar Faction H. Herwan Nasri, S.T and Mr. Drs. H. Tarmizi Muhammad.Based on the results of field research that researchers do produce conclusions Political Communication member DPRD Pekanbaru Golkar Faction In the process of political communication in addition to closer to the community, convey political messages that will affect the audience with political messages delivered, convincing people with vision- mission that has been done before the political communication process. In the process of political communication is measured through several indicators of political communication process involving good communication elements with the community, successful teams, parties and journalists as well as elements of print, online and social media.Keywords: Political Communication, Member of DPRD Pekanbaru City, Golkar Faction